Nanostructured γ-Al2O3 Synthesis Using an Arc Discharge Method and its Application as an Antibacterial Agent against XDR Bacteria - Awatif Rashed Z. Almotairy; A. M. Amer; Hadir El-Kady; Bassma H. Elwakil; Mostafa El-Khatib; Ahmed M. Eldrieny (Inorganics, 2023)
In the last few years, many efforts have been devoted to investigating the antibacterial activity of metal nanoparticles, especially against multidrug-resistant bacteria. Recently extensively drug-resistant (XDR) bacteria have emerged and caused a global threat. The purpose of this manuscript was to synthesize nanostructured γ-Al2O3 as an antibacterial agent against some XDRs. The results showed that Al2O3 was a mix of rod and spherical shapes in the nano range with diameters of less than 30 nm. The zeta potential was determined to estimate the surface charge for the synthesized γ-Al2O3, which was recorded as −34 ± 1.8 mV, indicating good stability. The synthesized nanostructured γ-Al2O3 showed a potent antibacterial activity against extensively drug-resistant Acinetobacter baumanii, with an inhibition zone diameter that reached 19 mm and a minimum inhibitory concentration (MIC) value that reached 2 µg/mL. The observed antibacterial activity of the prepared Al2O3 nanoparticles confirmed that the main mechanistic actions include bacterial cells apoptosis, ROS increment, cellular membrane disruption, and DNA damage. The cytotoxic effect (CC50) of the prepared γ-Al2O3-NPs was 1250 µg/mL in a normal human lung fibroblast cell line (WI-38 cells). It can be concluded that the synthesized γ-Al2O3 had an acceptable toxicity, which may pave the way for its use as a potent agent in the fight against XDR bacteria.